Regulation of Waste Management and Elimination of Accumulated Damage in the Countries of the Eurasian Economic Union - NAVASARDOVA, Eleonora Sergeevna; ZAHARIN, Andrey Nikolaevich; KOLESNIKOVA, Kira Vladimirovna; NUTRIKHIN, Roman Vladimirovich; SHINKAREV, Vladimir Aleksandrovich (Journal of Environmental Management and Tourism, 2021)
The article has been devoted to the analysis of waste legislation and the elimination of accumulated damage, as well as the practice of applying such legislation in the countries of the Eurasian Economic Union. The article considers the Basel Convention on the Control of Transboundary Movements of Hazardous Wastes and their Disposal of 1989, to which all the Eurasian Economic Union member states are currently parties. The question of the impact of the Basel Convention on their national legislation has been raised. The legislative gaps and shortcomings of the statutory regulation of waste management, as well as the elimination of accumulated damage in each of the Eurasian Economic Union countries, have been identified. The most successful legal novelties in this area of relations have been identified. Recommendations on their borrowing by other Eurasian Economic Union countries have been formulated. Significant problems have been identified in the relevant Russian legislation, as well as in the practice of its application. Proposals for their elimination have been formulated. Another identified problem, which is extremely relevant for the Eurasian Economic Union countries – is the definition of entities responsible for the elimination of accumulated damage on land plots, the ownership of which is not delimited. In such cases, it has been proposed to consider local self-government bodies responsible for the elimination of accumulated damage in such territories .